Functional connectivity of the posterior hippocampus is more dominant as we age - Blum, Sonja (Cogn Neurosci, 2014)
The role of the hippocampus in memory is dependent on its interaction with distributed brain areas. Anterior and posterior hippocampus have different roles in memory processing, and are impacted differently by aging in terms of structural decline, however functional connectivity of these hippocampal regions in aging is not well understood. Young (age 17-30) and aging (age 60-69) cognitively normal subjects underwent resting-state functional MRI revealing a shift from anterior hippocampus dominant hippocampus connectivity in younger age to posterior hippocampus dominant connectivity in aging subjects. We identified a subset of neocortical regions that are connected to the anterior hippocampus in younger adults but to the posterior hippocampus among older subjects, suggesting an age related reorganization of hippocampal networks supporting normal cognitive function. We also performed volumetric analysis which revealed no significant structural differences between groups. These findings provide evidence that “functional anatomy” which supports normal memory performance changes across the life span.